Plasma concentrations of etonogestrel in women using oral desogestrel before and after Roux‐en‐Y gastric bypass surgery: a pharmacokinetic study. (16th November 2018) - Ginstman, C; Frisk, J; Carlsson, B; Ärlemalm, A; Hägg, S; Brynhildsen, J
Abstract : Objective: To investigate whether Roux‐en‐Y gastric bypass (RYGB) affects oral desogestrel (etonogestrel) pharmacokinetics. Design: Single centre, open label, phase‐2 pharmacokinetic study. Setting: University hospital of Linköping, Sweden. Population: Fourteen women with planned RYGB surgery were included; nine women aged 18–45 years using 75 micrograms desogestrel completed the study. Methods: Steady‐state etonogestrel pharmacokinetic (PK) parameters were measured on three occasions for each individual (at 8 ± 6 weeks before surgery, and at 12 ± 2 and 52 ± 2 weeks after surgery). Each patient served as her own control. On each occasion, serum samples were collected during a 24‐hour period and etonogestrel concentrations were determined with ultra‐performance liquid chromatography/tandem mass spectrometry. Main outcome measures: Area under the plasma concentration time curve of etonogestrel ( AUC 0–24 hours ). Results: All women had significant postoperative weight loss. There were no significant differences in AUC 0–24 hours, terminal half‐lives ( t ½ ), time to peak serum concentrations ( T max ), or apparent oral clearances of etonogestrel (CLoral ) before and after gastric bypass surgery on any occasion. Peak serum concentrations ( C max ) increased after 52 ± 2 weeks compared with preoperative values (0.817 ng/ml versus 0.590 ng/ml, P = 0.024). Conclusion: To our knowledge, this is the first study to investigate the effects on desogestrel pharmacokinetics after RYGB. This study did not reveal any clinically significant changes in etonogestrel pharmacokinetics, suggesting that oral desogestrel may be used by women after RYGB surgery. The sample size was limited, however, and therefore the results should be interpreted cautiously. Tweetable abstract: The pharmacokinetics of oral desogestrel does not appear to change after gastric bypass surgery. Tweetable abstract: The pharmacokinetics of oral desogestrel does not appear to change after gastric bypass surgery.